The relationship between vegetation and soil moisture reveals the vegetation carrying capacity threshold—A case study of a Haloxylon ammodendron plantation in the Alxa desert, China - Zhou, Dongmeng; Si, Jianhua; He, Xiaohui; Jia, Bing; Zhao, Chunyan; Wang, Chunlin; Qin, Jie; Zhu, Xinglin; Liu, Zijin (Frontiers in Environmental Science, 2023)
Afforestation is an important and effective way to curb wind-sand hazards in the Alxa Desert. However, over-afforestation makes soil drying occur frequently. The formation of a soil drying layer is seriously restricting the effectiveness of vegetation construction and regional ecological stability. To clarify the process of soil desiccation in Haloxylon ammodendron plantations and determine the suitable planting years, a typical H. ammodendron plantation in this area was selected as the research object, and the soil moisture variation characteristics of this sand-fixing vegetation region with vegetation age were analyzed. The analysis results on soil water supply, consumption, and balance showed that the soil water storage in 0–400 cm soil layer of H. ammodendron plantation varies significantly in different ages. The soil water storage in 0–11 years old was the largest, and the soil water supply was greater than the soil water consumption. The soil water storage in profile increased with the increase of precipitation, the soil water storage of H. ammodendron at 11–22 years old increased first and then decreased with precipitation, and the inflexion existed in 16.5 years old. The soil water consumption of H. ammodendron plantation at 22–46 years old was greater than that of soil water supplement, and the soil moisture appeared negative balance continuously. Therefore, to prevent further deterioration of soil moisture ecological environment in the H. ammodendron plantation and to promote the sustainable development of afforestation in desert areas, thinning measures are suggested when the growth period reaches 16.5 years. The research results could provide scientific basis for afforestation and soil dry layer regulation in the Alxa desert.